Vertical tax competition in Brazil: evidence empirical to x ICMS IPI the period 1995 to 2009 - Rodolfo Herald da Costa Campos (2012)
The main objective of this study is quantify the impact caused by changes in federal tax on the tax policy of the states, considering the presence of horizontal tax competition between states. In federal systems, where various levels of government operate simultaneously in the same tax regime, setting tax rates on the same basis of taxation, there may be the existence of externalities. In that sense, the tax policy of a government level affects the size of the tax base of another level. Using a panel data covering 26 Brazilian states plus the Federal District for the period 1995-2009, it was estimated two models that represent the average reaction of state taxes in response to changes in federal tax rates, considering horizontal tax competition as a relevant variable in the model. The first model assumes that both levels of government act together simultaneously in setting its taxes rates (Cournot-Nash Model). The second model assumes that states react with delay to changes in federal taxes, as if this act as a Stackelberg leader in setting their tax (Model Stackelberg). The results indicate a positive response from the states to significant increases in the federal tax rate, in the presence of horizontal tax competition between states, resulting in a overtaxation tax base common to high taxes rates. The results of the J test proposed by Davidson and MacKinnon to choose the model indicate that state and federal adjust their rates both together as in a Cournot-Nash game.